IMPACT OF FLY ASH ON MECHANICAL PROPERTIES OF CLAY SOIL AND CBR VALUE: DAMPAK FLY ASH TERHADAP SIFAT MEKANIS TANAH LEMPUNG DAN NILAI CBR - Abadi Laia, Rahmat (LPPM UPMI, 2024)
This study aims to review the literature related to the impact of fly ash application on clay soil, with a particular focus on changes in soil mechanical properties and California Bearing Ratio (CBR) values. Fly ash, a by-product of coal combustion, has been widely used in civil engineering as a soil stabilization material. This study reviews various studies that have been conducted to understand how the addition of fly ash affects soil classification properties, such as plasticity and density, and increases the CBR value, which is an indicator of the soil's ability to withstand loads. The results of this review indicate that the addition of fly ash can significantly improve the stability and strength of clay soil, making it a more suitable material for use in road construction and other infrastructure. However, the specific impact of fly ash varies depending on the chemical composition of the fly ash and the characteristics of the clay soil used. This study also identifies several challenges and limitations in the use of fly ash, as well as recommendations for further research to optimize its use in soil stabilization.